Pretransplant immunotherapy increases acute rejection yet improves survival outcome of HCC patients with MVI post-liver transplantation - Xinjun Lu; Qi Zhu; Junfeng Cai; Zuozhong Yang; Guangxiang Gu; Li Pang; Mingye Su; Fapeng Zhang; Haoming Lin; Wenrui Wu; Leibo Xu; Chao Liu (Cancer Immunology, Immunotherapy)
Abstract Immune checkpoint inhibitor (ICI)-based immunotherapy has emerged as the most promising strategy for hepatocellular carcinoma (HCC) downstaging prior to liver transplantation (LT). However, further evidence is required to assess the feasibility and safety of pretransplant ICI exposure. We retrospective analyzed 159 HCC patients who underwent LT at our institution from June 2019 to December 2023, and 39 recipients (39/159, 24.5%) received pretransplant ICI therapy. The perioperative acute rejection rate and rejection-related mortality rate in the ICI group were 23.1% (9/39) and 12.8% (5/39), respectively, which were significantly higher than those in the non-ICI group, at 5% (6/120, P = 0.002) and 0% (0/120, P = 0.001). There was no significant difference in the 90-day post-transplant overall survival (OS) (P = 0.447) and recurrence-free survival (RFS) (P = 0.723) between these two groups. We found 37.1% (59/159) recipients were found to have microvascular invasion (MVI), no matter whether the HCC tumor is within Milan criteria or not. Notably, though MVI was identified as a risk factor for the LT recipients, pretransplant ICI exposure appeared to be a protective factor for HCC patients with MVI which benefits its overall survival. Besides, the RFS and OS in the ICI exposure recipients with MVI were comparable to the non-ICI exposure recipients without MVI. However, no synergistic anti-tumor effects were observed with pretransplant ICI immunotherapy when combined with locoregional of TACE, HAIC, RFA and systematic of lenvatinib or sorafenib downstaging treatments, nor with post-transplant adjuvant of systematic or FOLFOX chemotherapy. Further comprehensive studies are needed to balance the dual natural effects of immunotherapy by optimizing downstaging protocols and patient selection to reduce acute rejection and improve long-term survival.